2011
DOI: 10.1177/1420326x11417980
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Impacts of Exposure to Carbon Monoxide From Gas Appliances in UK Homes – Are We Missing Something?

Abstract: Carbon monoxide (CO) is a colourless and odourless poisonous gas formed from the incomplete combustion of substances containing carbon. In the United Kingdom, over 22 million homes have mains or liquefied petroleum gas and consequently there is particular concern regarding potential CO poisoning resulting from malfunctioning domestic gas appliances. Although the number of reported cases of CO poisoning in the United Kingdom is relatively small, there is a high probability of misdiagnosis of the condition due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Gas is delivered to approximately 20 million homes in the UK; the reported cases of accidental death due to CO poisoning are approximately 50, while non-fatal injuries account for 200 cases each year (Tam et al, 2012). Similar figures were reported in an investigation led by Baroness Finlay which indicated that 4,000 people are diagnosed with low levels of CO exposure (All Party Parliamentary Carbon Monoxide Group, 2011).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Gas is delivered to approximately 20 million homes in the UK; the reported cases of accidental death due to CO poisoning are approximately 50, while non-fatal injuries account for 200 cases each year (Tam et al, 2012). Similar figures were reported in an investigation led by Baroness Finlay which indicated that 4,000 people are diagnosed with low levels of CO exposure (All Party Parliamentary Carbon Monoxide Group, 2011).…”
Section: Introductionmentioning
confidence: 70%
“…It is a colourless, odourless gas and as such is SASBE 3,1 difficult to notice, unlike natural gas, which has a smell added to aid its detection (Tuan et al, 1994;Tam et al, 2012). The main causes of CO in homes are when gas appliances have been poorly fitted, maintained or repaired but may occur if vents, flues and chimneys are blocked (CIEH, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being long-standing, concerns about the impacts on public health due to exposure to CO produced by gas appliances are still current [3]. Most accidents are due to insufficient air intake or the poor condition of gas appliance installation and exhaust.…”
Section: Exhaust From Combustion Appliancesmentioning
confidence: 99%
“…The kitchen window area is 1.80(w) Â 1.10(h) m 2 with an air permeability of q ¼ 1.4810Dp 0.645 [m 3 /h], according to local measurements. In the above air permeability results, the air flows from the outside to inside the flat e depressurization.…”
Section: Description Of the Building And Ventilation System Testedmentioning
confidence: 99%